(untitled) (Indonesian Journal of Civil Engineering Study, 2024)
The choice of transportation mode in traveling is influenced by many factors, including the condition of the transportation services used. This is a consideration for people in Semarang City in choosing a mode of transportation. This study aims to determine the characteristics of respondents who travel the Semarang - Yogyakarta route by choosing the mode of travel car, bus, and train. Respondents’ travel characteristics determine the selection of modes in Semarang City. In addition to travel characteristics, travelers include gender, age, education, profession or occupation, income and travel destination. Travel characteristics include fare, travel speed, accessibility, safety, comfort, and service. Mode selection analysis is based on multiple linear regression. The results of the analysis are known as many as 300 respondents who are dominated by women 68%, with ages between 17-25 years by 65%, the majority of the last education of SMA or SMK as much as 58%, the profession or occupation most as students and college students 59%. Average income below Rp. 2,000,000 (58%), users of transportation modes for tourism 44%, with very rare travel intensity (1-3 times a month) 70%. Respondents chose train mode due to fare, bus due to safety and travel car due to comfort. The model of mode selection characteristics of the Semarang-Yogyakarta route obtained from the mathematical model is Y₁ = 12.767 + (- 0.217)X₁ , Y₂ = 11.032 + 0.283X₅, Y₃ = 10.845 + 0.440X₄.